Trion-Polariton formation in single-walled carbon nanotube microcavities - Möhl, Charles; Graf, Arko; Berger, Felix J.; Lüttgens, Jan; Zakharko, Yuriy; Zaumseil, Jana (ACS photonics, 2018)
We demonstrate the formation and tuning of charged trion-polaritons in polymer-sorted (6,5) single-walled carbon nanotubes in a planar metal-clad microcavity at room temperature. The positively charged trion-polaritons were induced by electrochemical doping and characterized by angle-resolved reflectance and photoluminescence spectroscopy. The doping level of the nanotubes within the microcavity was controlled by the applied bias and thus enabled tuning from mainly excitonic to a mixture of exciton and trion transitions. Mode splitting of more than 70 meV around the trion energy and emission from the new lower polariton branch corroborate a transition from exciton-polaritons (neutral) to trion-polaritons (charged). The estimated charge-to-mass ratio of these trion-polaritons is 200 times higher than that of electrons or holes in carbon nanotubes, which has exciting implications for the realization of polaritonic charge transport.